(untitled) (Journal of Medical & Health Sciences Review, 2025)
Lactobacillus plantarum is a significant probiotic species known for its ability to produce various active compounds. This research aimed to investigate the effects of Lactobacillus subtilis and Lactobacillus plantarum on amylase activity in Hypophthalmichthys molitrix. Three different diets were prepared for the experiment, labelled as Control group (T1) and two experimental groups (T2).The experimental fish were supplemented with varying concentrations of probiotics: the control group received 0% probiotics, T1 received 2.75% Lactobacillus subtilis and T2 received 2.45% Lactobacillus plantarum. Probiotics were administered twice daily. Weekly measurements of physio-chemical parameters such as water temperature, pH, dissolved oxygen, total hardness, total alkalinity, calcium and magnesium contents were recorded. At the end of each month, fish were dissected and their organs were isolated for evaluating amylase activity. The results revealed that amylase activity in T1 (30.389±1.76) increased significantly compared to T2 (28.7885±1.39) and the control group (28.22±1.25) over the duration of the trial. Among all treated groups, fish fed a diet containing 2.75% probiotics (T1) exhibited the highest amylase activity. Statistical analysis using ANOVA and correlation methods was employed to analyse the data related to amylase activity and physio-chemical parameters. The findings demonstrated that increasing the concentration of Lactobacillus subtilis and Lactobacillus plantarum significantly enhanced the amylase activity of silverfish.